Using WhatsApp for a homeless count. Issue 1 (2nd January 2017) - Calvo, Fran; Carbonell, Xavier
ABSTRACT: The study analyses how the use of instant messaging (WhatsApp) alongside other ICT tools is adequate to complement the count of homeless people in an area. In particular, it describes the methodology used in order to organize the first official count of homeless people in Girona (Catalonia, Spain). Given that this is the first count of individuals experiencing homelessness in the city, it is difficult to say that it is an improvement, but it could be suggested that the app might make the future counts more efficient. Both professional and volunteers and homeless people used WhatsApp to send information. A total of 283 homeless people were detected. Results show that the usage of this application optimized the results of the count. 36.1% of the data were obtained online. Homeless people, who were reluctant to contact directly with the professional team, used WhatsApp to communicate with them, adding up to 19.4% of the data obtained. Results show how communication between homeless people and health and mental health services can be potentially improved with this type of application.